Large magnetocaloric effect and near-zero thermal hysteresis in the rare earth intermetallic Tb1−xDyxCo2 compounds. (12th December 2016) - Zeng, Yuyang; Tian, Fanghua; Chang, Tieyan; Chen, Kaiyun; Yang, Sen; Cao, Kaiyan; Zhou, Chao; Song, Xiaoping
Abstract: We report the magnetocaloric effect in a Tb1− x Dy x Co2 compound which exhibits a wide working temperature window around the Curie temperature ( T C ) and delivers a large refrigerant capacity (RC) with near-zero thermal hysteresis. Specifically, the wide full width at half maxima ( δ WFHM ) can reach up to 62 K and the RC value changes from 216.5 to 274.3 J Kg −1 when the external magnetic field increases to 5 T. Such magnetocaloric effects are attributed to a magnetic and structural transition from a paramagnetic and cubic phase to a ferromagnetic ( M S along [1 1 1] direction) and rhombohedral phase or ferromagnetic ( M S along [0 0 1] direction) and tetragonal phase.